How Firms in Prospectives BRICS Economies Develop Green Innovations for Corporate Financing - Anggara, Ali Akbar; Kaukab, M. Elfan; Imron, Ali (LP3M Universitas Putra Bangsa, 2025)
This study explores how green innovation influences corporate financing among firms in BRICS economies, with a focus on Indonesia. Using panel data from listed Indonesian companies between 2010 and 2022, we investigate the effects of green process innovation, environmental R&D, and green patents on both debt and equity financing. Employing System GMM, the results show that all three types of green innovation significantly and positively affect firms’ access to capital. Green patents have the strongest impact on equity financing, while green processes and R&D contribute to improved debt financing conditions. Control variables such as firm size, asset tangibility, and liquidity also play important roles. The findings suggest that green innovation is not just an environmental commitment but a financial strategy that strengthens capital access and investor confidence. This has implications for both policy and corporate strategy, urging stakeholders to integrate green innovation as a core financial asset.